RETRACTED: Understanding the Typology and Basis of Traditional Attire in Cameroon: A Case Study of Kedjom Keku Fondom, 1936–2022 - Wihbongale, Louis Aghogah; Kom, Zongho (International Journal of Humanities, Education, and Social Sciences, 2025)
The traditional regalia of the Bamenda Grassfields represents a vital component of cultural heritage, garnering both national and international recognition. Distinguished by its fashionable appeal, this attire is often favored over Western clothing for significant cultural events such as traditional weddings and annual festivals. The intricate designs embedded and embossed on the cloth serve as symbolic representations of the identity, heritage, and cultural values of the Bamenda Grassfields communities. In the Kedjom Keku Fondom, embroidery was traditionally dominated by men; however, a gender shift has occurred, with women increasingly participating in the craft due to its economic viability and market-driven potential. As the popularity of the regalia has grown alongside increased participation in cultural and social events, both the demand and stylistic patterns have evolved, an area that has received limited scholarly attention. This paper argues that the production and use of Kedjom traditional regalia are dynamic processes influenced by changing demands and modern fashion sensibilities. Utilizing both primary and secondary sources and applying a qualitative, descriptive analysis, the study is organized into two main sections: the first explores the typology of Kedjom traditional attire, while the second examines the socio-cultural and economic bases underpinning its use. Findings reveal that regalia production is mutable and responsive to various social, cultural, and economic factors. Beyond its aesthetic function, traditional attire in Kedjom reflects identity, status, authority, livelihood opportunities, and income generation, highlighting its multifaceted significance in contemporary society.